Revitalising residential and foster care: new horizons in the 21st Century: 7th EUSARF International Congess, Trondheim, Norway, 11 – 14 September 2002 - Kirstie Maclean (Scottish Journal of Residential Child Care)
The European Scientific Association for Residential and Foster Care for Children and Adolescents (EUSARF) held its 7th International Congress in the ancient Norwegian capital of Trondheim. SIRCC made a good showing at the congress, with papers presented by Ian Milligan, Andy Kendrick and myself. There was a wide and varied programme with presentations from practitioners and researchers from across Europe, as well as from the USA, South Africa and New Zealand. It was reassuring, although also disappointing, to discover that other countries still wrestle with many of the same problems as we do in Scotland.